Popolation Structure of Seagrass Species and Environmental Conditions in The Gerupuk Beach Area, Central Lombok - Firanza, Yozi Mazri; Syukur, Abdul; Mertha, I Gde (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Population structure is a description of conditions in a habitat. Population status in habitats can be categorized into 3 parts, including crisis, threatened and safe. The aim of this research is to analyze the population structure of seagrass species and environmental conditions in the Gerupuk Beach area, Central Lombok. Data collection used the line transect method with a square measuring 1m x 1m. The sampling technique uses a systematic random sampling method. The research results identified 4 species and 3 families. The family includes Potamogetonaceae, Hydrocharitaceae, and Cymodoceaceae. Species in the family, namely Syringodium isoetifolium, Cymodocea rotundata, Halophila avails, and Enhalus acoroides. Environmental conditions in the Gerupuk Beach area, such as temperature, salinity, and pH, are within the range that supports seagrass growth. Temperatures range between 28-30˚C and salinity 25-35‰, in accordance with optimal seawater standards for seagrass ecosystems.